Terapi Musik Electronic Dance Music (EDM) dan Selawat pada Penderita Halusianasi Audio-Visual: Studi Kasus - Damar Irza; Aat Sriati; Iceu Amira (Lembaga Pengembangan Kinerja Dosen, 2024)
Seeing a frightening image or hearing a voice as a result of hallucinations often causes a person to be disturbed, which has an impact on the individual's ability in the work environment, relationships with partners, and fulfilling daily life needs. One intervention used for people with audio-visual hallucinations is music therapy. Music therapy is carried out by the nurse on duty in the room for ± 20 minutes with music requested by the client (which tends to be music that is liked). At the beginning and end of the study, an assessment of audio-visual hallucinations was carried out with the Washington Early Recognition Center Affectivity and Psychosis (WERCAP) Screen. Significant change from audio-visual hallucinations with initial WERCAP score 78 to 28 (score > 30: high risk of psychotic disorders). It is proven that Electronic Dance Music (EDM) and selawat will tend to get clients' attention. In effect, hallucinations: audio-visual, anxiety, non-aggressive behaviour, eating habits and indiscriminate defecation will eventually decrease over time. Further research is needed regarding the categories of music that people like, remembering that each person has their music preferences. This can strengthen the findings in this case report study or provide new contradictory evidence.